Childhood obesity - risk factors and prevention strategies - Barbara Magiera; Jakub Rybak; Karol Magiera; Piotr Bator; Michał Razik; Patrycja Rozwadowska; Jan Ramian; Wiktor Razik (Kazimierz Wielki University, 2024)
Introduction and purpose: Obesity is one of the most serious health challenges in modern society. Over the last 40 years, the number of obese school-age children has increased tenfold. This not only has significant consequences for physical health, but also affects psychosocial aspects and the quality of life of the young generation. The aim of this study is to conduct a comprehensive review of the literature on obesity among children and adolescents, focused on identifying the main risk factors and analyzing effective forms of prevention. Materials and methods: A review of the literature available in the "PubMed" database and books was conducted. The search was performed by using the following keywords: "childhood obesity", "childhood obesity risk factors", "childhood obesity prevention" State of knowledge: The risk factors for obesity in children and adolescents include genetic factors, endocrine diseases, improper diet, low physical activity, low socioeconomic status, stress, psychological factors, short sleep time, medications, hypothalamic obesity and H. pylori. As part of the prevention of obesity in children and adolescents, it is recommended to develop appropriate habits in children and adolescents. The influence of parents on health behaviors in children is important. Top-down activities such as health campaigns and legal regulations also have a significant impact. Summary: Due to research conducted over the years, awareness of obesity risk factors has increased. To effectively prevent this disease, an integrated approach is necessary, taking into account both education and changes in the social environment. Implementing these strategies requires cooperation at local, regional, national and international levels.